(untitled) (Development Service Industry Management, 2023)
Modern communication, both at the level of society and an enterprise, is accompanied by conflicts. The nature of conflict is the incompatibility of the goals of one entity with the goals of another entity, which is a natural inherent feature of human relations. The way a person reacts to a conflict determines the negative or positive outcomes of any conflict. For this reason, it is business leaders who have the opportunity to resolve conflicts with the most significant positive effect if they have complete information about the nature of conflicts, their sources, ways of responding to them, and resolving them. Conflict presents challenges but also presents rich opportunities for improved relationships and problem-solving. Skillful management of conflicts is an invaluable skill for everyone in leadership positions. For this reason, the study proposes to evaluate and consider the importance of communication with five conflict management styles in an organization according to the TKI model (Thomas Kilman Model). The research emphasizes the need for effective communication skills in managerial situations to resolve conflicts and optimize work. The research was based on a survey of twenty-two employees and managers with long-time experience in different organizations who have had their share of conflict and have a grasp on managing conflicts. The results of the investigation demonstrate that out of the five proposed conflict resolution styles according to the TKI model, the most significant number of respondents lean towards the collaborative style (working towards a goal), which is appropriate in conflict management, and that for collaboration to be practical, the need for fast and effective communication is critical. However, some organizations may focus less on conflict, which can have negative consequences and affect the morale of all stakeholders, including employees and employers. Based on the survey, the TKI model is the optimal conflict management approach. Consequently, developing practical communication skills is crucial for managers, administrators, and stakeholders to manage conflicts and enhance productivity.